When being good is not enough: Towards contextual education of business leadership ethics - Audur Hermannsdottir; Olga Stangej; Kari Kristinsson (Management: Journal of Contemporary Management Issues, 2018)
In light of continuing leadership scandals, ethics education has become a recurrent topic in public discourse. However, advancement of educational models, formats, and content rest with a number of questions that remain unanswered and subject to mixed research results. In this study, we contribute to the discourse on ethics education and its fundamental questions on the role of education in shaping attitudes towards business ethics. Through a survey of 61 students in Iceland, we examine the attitudinal differences between business and non-business students, and the effects of education. The results of the study indicate that education of the future business leaders calls for a contextualized approach to business ethical dilemmas. The study yields implications for secondary and tertiary levels of education.